Reflections on the Arab Uprisings - Samir Makdisi (Revue Internationale de Politique de Développement)
This chapter offers reflections on the Arab uprisings grouped under four headings: (1) the entrenchment of autocracy in the region, (2) the unravelling of autocracy, (3) the uncertainty of the transition process, and (4) the challenges of sustaining democratic transitions.   Among the primary factors underlying the general entrenchment of Arab autocracy, at least prior to the uprisings, are the relative abundance of oil resources and the region’s multi-faceted conflicts, along with all their attendant disruptive foreign interventions. Youth unemployment rising to very high levels and the persistence of deep economic inequality were important factors contributing to the uprisings. They were also reinforced by long frustrated aspirations for greater freedom and political participation on the part of social groups that have felt largely excluded from the benefits of economic development.   As of late 2016 the outcome of the uprisings remains highly uncertain especially with the rise to power of strictly fundamentalist groups and the ensuing armed conflicts that have come in their wake. The struggle between forces pushing for a move towards democracy and those pushing for the maintenance and/or regeneration of autocracy is presently in full play.   Transition experiences point to two fundamental challenges facing the consolidation of democratic transitions: firstly that the political victors be able to move in the direction of establishing genuinely representative and accountable political institutions. Secondly that they succeed in implementing an inclusive socio-economic strategy that not only focuses on growth and expanding employment opportunities but also eliminates ‘elite capture’ of the public sector.